Research on joint clearing of energy and ancillary service in the day-ahead market considering the weights of ancillary services - Mo, Dong; Chen, Mingyuan; Li, Qiuwen; Yang, Youhui; Wang, Ziqiang; Zhu, Xuefeng (Frontiers in Energy Research, 2025)
IntroductionWith the large-scale grid integration of renewable sources and the increasing number of new types of loads, the demand for ancillary services in the power system has been growing rapidly. Coordinated operation between the electric energy market and the ancillary service market has become a key research topic. Traditional independent and joint clearing mechanisms each have limitations under different resource conditions.MethodsThis paper proposes a novel joint clearing model that incorporates the weights of ancillary services. The model is constructed based on security-constrained unit commitment (SCUC) and security-constrained economic dispatch (SCED), integrating electric energy and ancillary services (frequency regulation, ramping, and spinning reserve) into a unified optimization framework. A penalty-weight mechanism is introduced to dynamically adjust the clearing priority of each ancillary service.ResultsUsing the IEEE-30 bus system as a test case, comparative simulations were conducted under scenarios of resource abundance and scarcity. The results show that the proposed model achieves significant cost reduction and more targeted ancillary service allocation compared with traditional independent and joint clearing models.DiscussionThe proposed clearing mechanism retains the global efficiency of joint clearing and the dispatch priority of independent clearing by incorporating ancillary service weights. It demonstrates adaptability to different resource conditions and enhances system flexibility and reliability. This model provides a promising solution for future power systems with high renewable penetration.